2021
DOI: 10.20517/mtod.2021.13
|View full text |Cite
|
Sign up to set email alerts
|

MAFLD AND NAFLD: is there the need for redefining the risk of cardiovascular disease and mortality?

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide and is characterized by a high burden of metabolic alterations. It exposes patients to increased morbidity and mortality, mostly driven by cardiovascular (CV) complications. Despite its large use, the nomenclature NAFLD has some limitations, due to the exclusion of patients with hepatic fat and concomitant other liver diseases or moderate alcohol consumption possibly contributing to hepatic damage. Therefore, a new and more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Given the metabolic hallmark of the new definition of MAFLD, it could be speculated that an increased risk of cardiovascular complications should be expected in this subtype of NAFLD [37]. Indeed, despite data about cardiovascular abnormalities in MAFLD are limited, it has been showed that individuals with MAFLD phenotype had a substantially increased ASCVD risk compared to those without MAFLD [38].…”
Section: The Intricate Relationship Between Nafld and Cardiometabolic...mentioning
confidence: 99%
“…Given the metabolic hallmark of the new definition of MAFLD, it could be speculated that an increased risk of cardiovascular complications should be expected in this subtype of NAFLD [37]. Indeed, despite data about cardiovascular abnormalities in MAFLD are limited, it has been showed that individuals with MAFLD phenotype had a substantially increased ASCVD risk compared to those without MAFLD [38].…”
Section: The Intricate Relationship Between Nafld and Cardiometabolic...mentioning
confidence: 99%